1995
DOI: 10.1017/s0950268800058489
|View full text |Cite
|
Sign up to set email alerts
|

The transmission of Jembrana disease, a lentivirus disease of Bos javanicus cattle

Abstract: SummaryMethods of transmission of Jembrana disease, an acute and severe disease of Bali cattle (Bos javanicus) caused by a recently-identified bovine lentivirus known as Jembrana disease virus, are described. During the acute disease virus can be detected in saliva and milk. There is evidence of direct transmission from acutely affected animals in close contact with susceptible cattle, possibly by virus in these secretions infecting cattle by the conjunctiva!, intranasal or oral routes, by which it was possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
10
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 11 publications
5
10
0
Order By: Relevance
“…In experimentally JDV-infected Bali cattle, the death rate was about 21% (Soesanto et al, 1990;Soeharsono et al, 1990). This finding was supported with evidence acquired in several epidemiological studies (Soeharsono et al, 1995a;1995b;Chadwick et al, 1998). In lethal infection, mortality was occurred within only 1 to 2 weeks after infection and was correlated to multiorgan failure Wilcox, 1997).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In experimentally JDV-infected Bali cattle, the death rate was about 21% (Soesanto et al, 1990;Soeharsono et al, 1990). This finding was supported with evidence acquired in several epidemiological studies (Soeharsono et al, 1995a;1995b;Chadwick et al, 1998). In lethal infection, mortality was occurred within only 1 to 2 weeks after infection and was correlated to multiorgan failure Wilcox, 1997).…”
Section: Introductionsupporting
confidence: 79%
“…During the acute phase, high titer of infectious JDV viral particles is found in plasma (Kusumawati et al, 2014b). Viruses are also abundantly present in secreted fluids, namely milk and saliva (Soeharsono et al, 1995b). This make viral antigen identification by molecular method is ideal detection tool in order to detect viral infection as early as possible during the course of the disease.…”
Section: Future Directionmentioning
confidence: 99%
“…The majority of animals develop detectable antibodies to the virus only 6 weeks or more after recovery from the acute phase of the disease (17,41). Surviving animals are resistant to reinfection, remain infectious for at least 2 years, and do not appear to suffer further episodes of disease (35).…”
mentioning
confidence: 99%
“…Attempts to cultivate JDV in vitro have been unsuccessful (42), and this has restricted the development of assays for the quantification of infectious virus. A series of animal bioassay experiments reported by Soeharsono et al (35) provide the only data available regarding virus replication during the acute phase of disease process. These studies revealed that there was a high titer of infectious virus in plasma of about 10 8 50% cattle infectious doses (ID 50 )/ml during the acute febrile period, decreasing to low levels and persisting at low levels in recovered animals.…”
mentioning
confidence: 99%
See 1 more Smart Citation